Analysis of Learning Motivation of Junior High School Students in Science Learning in Surabaya City - Damayanti, Martha; Hidayati, Siti Nurul (Jurnal Pijar Mipa, 2025)
Student learning motivation is an important factor that influences the success of the learning process. This study aims to analyze the learning motivation of junior high school students in Surabaya City, especially in science learning, without the intervention of a particular learning model or approach. This research design uses a survey design with quantitative data collection methods. The learning motivation instrument is a learning motivation questionnaire containing 12 statements based on ARCS indicators: attention, relevance, confidence, and satisfaction. The sample of this study consisted of 88 students, 32 female students and 56 male students, and the sampling technique used was cluster sampling. The data obtained were analyzed descriptively quantitatively using a Likert scale to determine the average of each indicator of student learning motivation. The results showed that the average student learning motivation reached 71% and was classified in the high category, indicating that students have a fairly good learning motivation in science learning. Therefore, it can be concluded that this research indicates that students' overall learning motivation is on the good criteria. Unfortunately, good criteria did not occur in all indicators, where the confidence indicator showed the lowest score, so there is a need to improve the confidence aspect of students so that they are more active and confident in the learning process, such as using student-centered learning models.